Spread of Xanthomonas campestris pv. musacearum in banana plants: implications for management of banana Xanthomonas wilt disease - Adikini, S.; Beed, Fenton D.; Tusiime, Geoffrey; Tripathi, L.; Kyamanywa, S.; Lewis-Ivey, M.; Miller, S.A. (Informa UK Limited, 2013)
Banana Xanthomonas wilt (BXW) caused by Xanthomonas campestris pv. musacearum (Xcm) is a devastating disease of bananas in Uganda and across the Great Lakes region of East and Central Africa. While use of disease-free suckers is recognized as important to control BXW, bacterial movement from infected mother plants to their suckers is not well understood. In this study, the movement of Xcm through the pseudostem of naturally and artificially infected bananas was examined. In naturally infected plants, samples of plant organs collected from susceptible cultivars ‘Kayinja’, ‘Nfuuka’ and Kivuuvu’ (Musa acuminata) at various stages of disease were analysed using a polymerase chain reaction assay employing Xcm specific primers. Xanthomonas campestris pv. musacearum was detected in 70% of asymptomatic corms and suckers collected from each of the three susceptible cultivars. In ‘Kayinja’ and ‘Nakitembe’, Xcm was recovered from plant parts 20 cm away from the point of inoculation prior to symptom development. The population of Xcm was variable within and among the plant parts over time, with the highest number being recorded in the inoculated region for all cultivars. No disease was observed seven days after inoculation of the Xcm-resistant wild species M. balbisiana and Xcm was restricted to the point of inoculation. This study implies that by the time wilt symptoms are expressed, Xcm has migrated from the point of entry to most parts of the plants. Use of suckers from infected plants should be restricted as they are likely to be latently infected and could thus result in disease when transplanted.